DISTRIBUTION OF DIPHYLLOBOTHRIUM LATUM IN THE POPULATIONS OF PIKE IN LAKES OF TRANSBAIKALIA - Zh. N. Dugarov; O. B. Gaponova; L. V. Tolochko (Российский паразитологический журнал, 2016)
Objective of research. The aim of the study was to explore the degree of contamination of pike and other fish species, plerosarcoidoma Diphyllobothrium latum in water bodies of the Baikal region. Materials and methods. In 2009-2014 was conducted parasitological study on infestation role of the D. latum plerocercoids of various species of fish. Just investigated 20 specimens of pike, 38 – burbot, 91 – perch and ruff 73 specimens in lakes of the North-Eastern part of Transbaikalia, located located in different districts of the Republic of Buryatia. The infection of fish with plerocercoids of D. latum were evaluated by extensiveness (EI), the abundance index (EI) and the intensity of infection (AI). Results and discussion. The pike infestation with plerocercoids of D.latum in lake. Goose in 2013-2014 decreased in 3 times compared with a maximum in 1973-1974 and was 0.8 % most Often, the D. latum plerocercoids are localized in the adipose tissue, the gonads, the wall of the swim bladder, liver, peritoneal epithelium, muscle, the wall of the stomach and the village-since respectively 40,9 %; 13,8; 9,1; 9,1; 9,1; 4,5; 4,5; 4,5 and 4.5 % of cases. In Transbaikalia the fish  parasitize three species of tapeworms, of which the epidemiological importance of the D. latum, D. dendriticum. D. ditremum in humans does not develop until the adult stage. In the region annually celebrate 150-450 cases of difillobotrioza in humans. In the basin of the Selenga river is-the reputed source of human infection by difillobotrioza are pike and perch, the infected with its goodAzerbaijani D. latum and the Baikal omul Coregonus migratorius infected with D. dendriti-cum. EI Baikal omul D. dendriticum is 62.3-100 %, and IO – 4,0-9,8 copies of This cestode is brought in the Selenga river from oz. The Baikal in the autumn spawning of Arctic Cisco. On owasco-FDI sample of human feces is impossible to distinguish the species D. latum and D. dendriticum. Probably in the Selenga region of Buryatia, there is a hotbed of difillobotrios caused by these two species of cestodes.